Thermal Limits and Decline of Synechococcus Under Accelerated Warming and Marine Heatwaves - Luthfiyyah Azizah; Eva Alou‐Font; Alexandra Coello‐Camba; Susana Agusti (Global Change Biology, 2026)
Marine picophytoplankton contribute roughly 20% of global oceanic primary production, including thermally resilient taxa such as Synechococcus , which dominate warm oceans and are projected to benefit from future warming. Tropical populations exist near their upper thermal limits, making them highly vulnerable to further warming, a largely unexplored risk for Synechococcus . Here, we combine high‐frequency in situ observations and laboratory experiments to examine the thermal tolerance of Synechococcus in the Red Sea, one of the warmest marine basins globally. Over a 7‐year period (2018–2024), we monitored population dynamics alongside continuous sea surface temperatures, capturing the increasing frequency and duration of marine heatwaves (MHWs) in 2023–2024, the warmest years on record. Abundance of Synechococcus increased with temperature and peaked at ~30.2°C, but extreme temperatures recorded in 2023–2024 substantially exceeded the range associated with maximum Synechococcus abundance. Laboratory experiments of Synechococcus clades isolated from the Red Sea, confirmed strain‐specific optima ranging from ~25°C (clade IIIa) to ~33°C (clade IIa), with maximum thermal limit up to 35.2°C. During the unprecedented warming of 2023–2024, when sea surface temperatures exceeded 35°C and MHWs persisted for up to 55 days, Synechococcus blooms weakened by ~4.5‐fold. Although the timing of Synechococcus blooms remained stable, warmer years were characterized by reduced abundances and lower bloom magnitude, indicating changes in population intensity rather than shifts in bloom timing. Comparison with published temperature–abundance models demonstrates prior datasets fail to capture responses to extreme warming. Our results provide direct evidence of ecological niche loss in tropical Synechococcus , challenging predictions of their future dominance and highlighting the vulnerability of even the most heat‐tolerant primary producers to accelerated warming. These findings underscore the capacity of extreme warming events to rapidly destabilize plankton communities, reduce primary production, and alter ecosystem function, emphasizing increasing uncertainty in forecasting ocean productivity under accelerating climate change.